A Comparative Study of Healthy Lifestyle of Iranian and Iraqi Elderly and Its Predictors - Sadegh Mohsen Al-Gimavi; Mahmoud Bakhshi; Akram Ghanbari Moghaddam; Vahid Ghavami; Hasanain Al-Khalidi (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives Lifestyle is influenced by differences in societies and changes in culture, social and environmental conditions, hence this study was conducted to determine and compare healthy lifestyle and its predictors in the elderly living in Iran and Iraq. Methods & Materials This descriptive-analytical study was performed on 800 elderly people over 60 years old who were referred to health centers in Najaf City, Iraq, and Mashhad City, Iran in 2021. The research units were selected by cluster probability sampling. Data were collected by demographic characteristic form, healthy lifestyle questionnaire for the elderly, and questionnaire of predictors of a healthy lifestyle at the time of the presence of the elderly in the health center. Data were analyzed using SPSS software, version 23 with descriptive statistics, and the Chi-Square, Mann Whitney U, independent t test, and regression. Results The Mean±SD age of the elderly in Iran and Iraq was 66.89±6.68 and 66.42±5.23 years, respectively. About 75% of the Iranian elderly and 59% of the Iraqi elderly had a moderate lifestyle. The mean and standard deviation of total lifestyle scores in Iran and Iraq were 145.75±14.97 and 152.29±13.46, respectively, and the independent t test showed a significant difference (P<0.001). Multiple linear regression tests showed that variables of age, self-assessment of health, drug abuse, income and job satisfaction, and marital status and companions had a significant relationship with a healthy lifestyle in the Iranian elderly, while in the Iraqi elderly, variables of age, sex, self-assessment of health, smoking, income, and job satisfaction, and companions had a significant relationship with a healthy lifestyle (P<0.05). Predictor factors predicted 25% of healthy lifestyle scores in Iran and 37% in Iraq. Conclusion It is recommended to improve the lifestyle of the elderly in both Iran and Iraq from the current situation to the desired level. For this purpose, health officials must pay more attention to the most effective factors for a healthy lifestyle, especially drug abuse and income satisfaction in Iran and Iraq, respectively.